Exploring teacher emotional intelligence and its impact on school climate - Morton, Cleion L. (Kansas State University, 2014)
Teachers and administrators are struggling. They must do more with less. Children come to school from a variety of backgrounds and experiences. These issues, as well as numerous others, provoke emotions that run rampant—sometimes out of control and sometimes minimized to the point of being destructive. In turn, the school climate and learning environment is affected. Teachers need support to enhance their understanding of emotional intelligence (EI). Application of EI competencies can positively influence school climate. The purpose of this intrinsic case study was to understand the perceived impact of enhancing teacher knowledge and application of emotional intelligence on school climate. The study explored teacher emotional intelligence, school climate, and the intersection of the two. Emotional intelligence instruction and education were provided to the teacher research participants during the study to support their personal growth. This study provided an understanding of the impact of teacher emotional intelligence on school climate. Results indicated that teacher emotional intelligence can be developed or enhanced and that it does affect their perception of the school climate. The impact was reflected in greater teacher awareness, intentional application of EI strategies, recognition of the benefits of EI on school climate, acknowledgement of factors impeding EI and school climate, and an altered perception of their role in the school climate. The study revealed a continued need for emphasizing and enhancing teacher emotional intelligence as a means of improving school climate. Utilizing a model such as the Six Seconds Model for Emotional Intelligence proved worth the time and effort because it enhanced teacher EI and changed teacher perceptions of school climate. A need for additional time and continued EI training was also noted as a means for additional growth in a more positive school climate.
Keywords: Emotional intelligence; School climate; Teachers; Six Seconds Model; Case study; Junior High; Educational Administration (0514); Educational leadership (0449); Education, General (0515)